IDENTIFIKASI ELEMEN ARSITEKTUR PADA FASAD BANGUNAN HERITAGE DI KAWASAN PECINAN SINGKAWANG, KALIMANTAN BARAT Studi Kasus: Bangunan Kolonial - Jamilatul Muna; Emilya Kalsum; Jawas Dwijo Putro (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2021)
Indonesian is a country that is rich in cultural diversity. Culture arises from a tradition and values that a society has over the years and as an important part of their character so that it becomes a legacy to create the next. This inheritance/heirloom is known as heritage.. A historic city/ area usually has a heritage building that becomes the image of an area. Among them is the chinatown area of Singkawang. Heritage buildings in the Singkawang city include colonial heritage buildings. The building has an important value for history, science, culture which deserves to be preserved and controlled so that in addition to learning material for architectural development in the future. The focus is focused on the formulation of architectural elemens on the facades of heritage buildings in Chinatown of Singkawang wich are related to the shape of the buildings and their ornaments. This study used a qualitative research method with a descriptive approach in order to describe the heritage buildings in the old city area Singkawang. The data was collected by means of observation, documentation (photographing research objects) and interview. The result of the research states that there are two classifications of heritage buildings in the Chinatown area of Singkawang, namely Chinese buildings and colonial buildings with façade composition of the facades of each heritage building.